Enhancing Character Education through the Implementation of Gamification in Learning - Hafsah; Zedi Muttaqin; Ratu Mutiara (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
Advancements in technology require educators to develop innovative learning media that not only enhance cognitive aspects but also strengthen students’ character development. This study aims to examine the effectiveness of gamification-based learning media in shaping the character of junior high school students in Mataram City using a quasi-experimental design. A total of 35 students were divided into two groups: an experimental group and a control group. Data were collected using a Likert-scale questionnaire, and analysis included normality testing and simple linear regression. The Shapiro-Wilk test confirmed that the data were normally distributed. Simple linear regression analysis revealed that 83.7% of the variation in students’ character could be explained by the use of gamification. Character improvement in the experimental group was more significant and consistent than in the control group. Gamification media proved effective in reinforcing character values such as honesty, responsibility, cooperation, and nationalism. These findings support gamification as an innovative learning strategy, with implications recommending its integration into the curriculum to strengthen character education in schools.